Introduction to the 35th International Conference on Logic Programming Special Issue. Issue 5 (September 2019) - ERDEM, ESRA; FORMISANO, ANDREA; VIDAL, GERMÁN; YANG, FANGKAI
Abstract : This volume contains the regular papers of the 35th International Conference on Logic Programming (ICLP 2019), held in Las Cruces, New Mexico, USA, from September 20 to September 25, 2019.